Decoding Anti-Identity: A Barthesian Analysis of Cultural Trauma in Philip Roth’s The Human Stain - Li, Na (Ilmu Inovasi Nusantara, 2024)
This study addresses the cultural and psychological trauma experienced by the protagonist, Coleman Silk, in Philip Roth’s The Human Stain (2000), particularly as an African-American navigating a white-dominated society during the Clinton era. The novel explores issues of racial discrimination, political correctness, and a prevailing spirit of persecution in American society, leading to Coleman’s eventual loss of self-identity and his tragic search for it. This study aims to analyze the anti-identity motif within Roth’s novel by applying Roland Barthes’ code theory. By decoding the various narrative elements and mysteries surrounding Coleman’s life and secrets, the study aims to reveal how these codes ultimately contribute to the novel’s central theme of anti-identity. This research utilizes textual analysis through the lens of Barthes’ code theory. Such an approach enables the identification of multiple narrative codes highlighting vital aspects of Coleman’s identity struggles and the novel’s broader themes of identity crisis. The findings suggest that the anti-identity motif is critical in The Human Stain. The secrets surrounding Coleman’s origins and identity drive the plot and the tragedies. Barthes’ theory helps unravel these narrative codes, emphasizing how they support the anti-identity theme in Roth’s work. The study recommends further research into the use of Barthes’ code theory to examine contemporary literature, especially in works that focus on identity crises within socially oppressive contexts marked by discrimination and normative pressures.